Are US Crime Rates Really Unit Root Processes? - Cook, Jemma (Journal of quantitative criminology, 2011)
Existing research has uncovered little evidence against the hypothesis of US crime rates being unit root processes, despite the uncomfortable implications of this assumption. In light of this, the present paper draws upon noted changes in the temporal patterns of US crime rates since 1960 to undertake an informed approach to testing of the unit root hypothesis which incorporates two potential points of structural change. The results obtained show the unit root hypothesis to be rejected for all classifications of criminal activity examined over the period 1960 to 2007. In addition, the dates of the detected breakpoints are supported by a variety of arguments available in the existing criminology literature concerning alternative determinants of crime and their movements. Interestingly, a difference is observed in the nature of the breaks detected for violent and property crimes. However, potential explanations for this are again found in theoretical arguments available in the criminology literature. Finally, the implications of the current findings for the properties of crime, its subsequent statistical analysis and past and future research are discussed.